2017
DOI: 10.7567/jjap.56.06hb08
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of precise control of surface reaction by new patterning technique for small-contact etching with TiN hard mask

Abstract: We introduce state-of-the art small-contact etching by a new patterning technique using atomic layer etching (ALE) for sub-5 nm technology generation. In small-contact etching, SiO 2 is etched by using a TiN hard mask with the progress of the miniaturization process. However, when applying the conventional method to small-contact etching with a TiN mask, etch stop is caused by excess deposition on the SiO 2 film. From the results of surface analysis by X-ray photoelectron spectroscopy (XPS) and transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[14][15][16][17][18][19][20] For example, ALE of SiO 2 was demonstrated by the FC radical deposition and Ar ion activation. 21,22) Similarly, the independent control over radical and ion flux has also been demonstrated in Si 3 N 4 etch using HFC gas chemistries. 23) Although more concise etch control can be obtained via ALE, multiple layers of FC and HFC can be accumulated depending on process recipes adsorption time.…”
Section: Introductionmentioning
confidence: 92%
“…[14][15][16][17][18][19][20] For example, ALE of SiO 2 was demonstrated by the FC radical deposition and Ar ion activation. 21,22) Similarly, the independent control over radical and ion flux has also been demonstrated in Si 3 N 4 etch using HFC gas chemistries. 23) Although more concise etch control can be obtained via ALE, multiple layers of FC and HFC can be accumulated depending on process recipes adsorption time.…”
Section: Introductionmentioning
confidence: 92%
“…[180][181][182][183] Tabata et al reported that a quasi-ALEt technique that controls radical flux and ion flux independently could resolve etching interruption (etch-stop) issues due to the reduction of excess deposition on small area in contact-hole of SiO 2 , when a TiN hard mask was conventionally used as occurred etch stop. 184) 186) In addition, the directional ALEt of GaN and AlGaN using cyclic Cl 2 plasma chemisorption and Ar ion removal was reported under conditions of low ion energy ranging from 50 to 100 eV within the self-limiting regime, as reported by Ohba et al 187) In contrast, isotropic etching includes a sequential process for ammonium-salt-based modified layer formation and thermal evaporation of the salt, as originally reported for SiO 2 removal by Nishino et al 188) The salt is essentially formed by a self-limiting reaction and remains on the reacted surface. Then, it is desorbed by thermal heating without leaving any residue on the surface.…”
Section: State-of-the-art Of Aletmentioning
confidence: 99%
“…For example, thinner films were deposited and higher etching rates were observed for silicon oxides and nitrides, while thicker films and lower etching rates were observed for silicon surfaces. 203,204) For the case of metal ALEt, low energy ion bombardment is useful in the self-limiting formation of a ligand-exchange layer. In Fig.…”
Section: Future Challengesmentioning
confidence: 99%